The Effect of Intramolecular Hydrogen Bond Type on the Gas-Phase Deprotonation of ortho-Substituted Benzenesulfonic Acids. A Density Functional Theory Study - Nina I. Giricheva; Sergey N. Ivanov; Anastasiya V. Ignatova; Mikhail S. Fedorov; Georgiy V. Girichev (Molecules, 2020)
Structural factors have been identified that determine the gas-phase acidity of ortho-substituted benzenesulfonic acid, 2-XC6H4–SO3H, (X = –SO3H, –COOH, –NO2, –SO2F, –C≡N, –NH2, –CH3, –OCH3, –N(CH3)2, –OH). The DFT/B3LYP/cc-pVTZ method was used to perform conformational analysis and study the structural features of the molecular and deprotonated forms of these compounds. It has been shown that many of the conformers may contain anintramolecular hydrogen bond (IHB) between the sulfonic group and the substituent, and the sulfonic group can be an IHB donor or an acceptor. The Gibbs energies of gas-phase deprotonation ΔrG0298 (kJ mol–1) were calculated for all compounds. It has been set that in ortho-substituted benzenesulfonic acids, the formation of various types of IHB is possible, having a significant effect on the ΔrG0298 values of gas-phase deprotonation. If the –SO3H group is the IHB donor, then an ion without an IHB is formed upon deprotonation, and the deprotonation energy increases. If this group is an IHB acceptor, then a significant decrease in ΔrG0298 of gas-phase deprotonation is observed due to an increase in IHB strength and the A− anion additional stabilization. A proton donor ability comparative characteristic of the –SO3H group in the studied ortho-substituted benzenesulfonic acids is given, and the ΔrG0298 energies are compared with the corresponding values of ortho-substituted benzoic acids.